Physical activity and cognitive performance in cancer survivors : a cross-sectional study - Marques, Mafalda Vasconcelos de Figueiredo (2024)
Cancer survivorship poses challenges beyond remission, with cancer-related cognitive impairment (CRCI) often affecting memory, attention, and executive function, impacting daily functioning and quality of life. Physical activity (PA) has shown positive effects on cognitive performance, with studies reporting improvements in cognitive function after high-intensity exercise and enhanced memory recall following moderate exercise. However, evidence regarding PA’s effects in cognition on cancer survivors remains mixed, possibly due to the reliance on selfreport cognitive questionnaires and the limited number of studies examining the influence of factors like depression and cognitive reserve (CR) on PA in this population. Therefore, this study aims to explore the relationship between regular ongoing physical activity and cognitive performance, and how it influences cognitive reserve and depression in cancer survivors. The sample of this study comprised 154 breast and lung cancer survivors. PA was selfreported and categorized by PA intensity levels. CR was measured with the TeLPI and the CRIq. Cognitive domains were evaluated as composite scores for attention and processing speed (APS), executive function (EF), and learning and memory (LM). For subjective cognitive complaints, the FACT-COG-v3 was used, while depressive symptoms were measured using the HAM-D. Results show no significant differences in cognitive performance across PA intensity levels. However, the very active PA group was positively associated with the leisure-time subscale of CRIq. No significant correlations were found between PA and depressive symptoms, although its severity was negatively associated with subjective cognitive complaints. These findings highlight the complexity of CRCI and the need for further longitudinal research to explore the effects of PA on cognition in this population and the influence of other possible factors such as CR.